Norepinephrine-Induced Calcium Signaling and Store-Operated Calcium Entry in Olfactory Bulb Astrocytes - Fischer, Timo; Prey, Jessica; Eschholz, Lena; Rotermund, Natalie; Lohr, Christian (Frontiers in Cellular Neuroscience, 2021)
It is well established that astrocytes respond to norepinephrine with cytosolic calcium rises in various brain areas, such as hippocampus or neocortex. However, less is known about the effect of norepinephrine on olfactory bulb astrocytes. In the present study, we used confocal calcium imaging and immunohistochemistry in mouse brain slices of the olfactory bulb, a brain region with a dense innervation of noradrenergic fibers, to investigate the calcium signaling evoked by norepinephrine in astrocytes. Our results show that application of norepinephrine leads to a cytosolic calcium rise in astrocytes which is independent of neuronal activity and mainly mediated by PLC/IP3-dependent internal calcium release. In addition, store-operated calcium entry contributes to the late phase of the response. Antagonists of both 1- and 2-adrenergic receptors, but not -receptors, largely reduce the adrenergic calcium response, indicating that both -receptor subtypes mediate norepinephrine-induced calcium transients in olfactory bulb astrocytes, whereas -receptors do not contribute to the calcium transients.